MORAL-ETHICAL PRINCIPLES OF GOVERNANCE IN ANCIENT EASTERN STATES: THE BABURIDS, SELJUQS, AND SAFFARIDS - Shonazarov Jamshid Shukhratovich (Innovate Conferences, 2025)
This paper investigates the moral-ethical principles underlying governance in the Baburid, Seljuq, and Saffarid states of the Ancient East. Integrating historical chronicles, philosophical treatises, and contemporary scholarship, the study analyzes how values such as justice, compassion, wisdom, and honesty shaped administrative culture, state-building traditions, and rulers’ legitimacy. The research applies comparative-historical methods to reveal both commonalities and distinctions in social ethics, bureaucratic accountability, and legal norms. Findings suggest lasting influence of spiritual ideals in governance across diverse regions and eras.
Keywords: Ancient East, Baburids, Seljuqs, Saffarids, ethics, governance, justice, social responsibility